Job quality of minimum wage workers in Ireland - Paul Redmond; Klavs Ciprikis; Elisa Staffa (The Economic and Social Research Institute (ESRI), 2023)
The provision of high-quality jobs is an important component of the policy strategy of organisations such as the ILO, the OECD and the European Union. Job quality can have important implications for employee well-being, as well as being an important component of a well-functioning and productive economy. Capturing the multidimensional aspects of job quality is difficult as many surveys do not capture the full range of job quality indicators. In this research, we combine three different datasets to examine the job quality of minimum wage workers in Ireland relative to higher paid workers across a range of dimensions. The datasets we use include the 2022 Irish Labour Force Survey, the 2015 European Working Conditions Survey, and the 2014 European Skills and Jobs Survey. As we are focused on minimum wage employment, which by definition are low-paying jobs, we focus on aspects of job quality beyond remuneration.
Keywords: 330; Arbeitsbedingungen; Mindestlohn; Irland